Treatment outcomes in malignant ovarian germ cell tumors - Kumar B., Ram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Malignant ovarian germ cell tumours are rare group of ovarian neoplasms derived from primordial germ cells of the ovary. Objective of present study was to evaluate the outcome of treatment in malignant germ cell tumours. Methods: 21 Patients of malignant ovarian germ cell tumours registered at Department of Medical Oncology, Institute of Obstetrics and Gynaecology, Chennai for the period from January 2012 to December 2015 were retrospectively analyzed for treatment outcomes. Results: The median age at presentation was 21 years with age range between 14 and 40 years. 9patients (43%) presented with mixed germ cell tumour, 6 patients (29%) with dysgerminoma, 3 patients (14%) with yolk sac tumour and 3 patients (14%)with mature cystic teratoma. 13 patients (62%) presented with Stage I disease, 5 patients (24%) with Stage III and 3 patients (14%) with Stage II. Fertility sparing surgery was done in 15 patients (71%), and 4 patients (19%) who completed family had TAH with BSO done. Adjuvant Chemotherapy was given for 16 patients (76%) and as Neoadjuvant in 2patients (10%) who had biopsy alone performed. 4patients (19%) developed recurrence and was taken for salvage PVI chemotherapy. Conclusions: Malignant ovarian germ cell tumours are relatively uncommon neoplasms characterized by high chemo sensitivity. This study confirms that malignant ovarian germ cell tumours have excellent prognosis and the effectiveness of BEP chemotherapy regimen. Fertility sparing surgery is feasible in most cases. Advanced Stage configured as an important risk factor for survival. The chemotherapy regimen was associated with significant but manageable toxicity.